Factors affecting the outcome of patients undergoing endoscopic septoplasty: a prospective study - Shah, Dhruvin; Sorathiya, Rashmi; Khilnani, Ajeet K.; Hirani, Narendra; Jain, Nikhil; Patel, Mansi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Background: A deviated nasal septum (DNS) refers to an abnormal displacement of the septum from the midline. Endoscopic septoplasty has gained popularity due to its minimally invasive nature and better visualization of the septal deformities. The nasal obstruction symptom evaluation (NOSE) score is a validated, patient-reported outcome measure used to assess the severity of nasal obstruction and the impact of surgical intervention. Methods: A randomized prospective clinical study was conducted with total of 81 patients of either gender, aged between 17 to 60 years, diagnosed clinically and radio logically with deviated nasal septum and scheduled for endoscopic septoplasty surgery from April 2023 to October 2024. The patients were evaluated for NOSE score. After undergoing endoscopic septoplasty patients were followed up weekly for 2 weeks and then every 15 days till 1.5 months. Post-operatively after 6 weeks NOSE score was calculated and it was compared with the preoperative score. Results: The study included total 81 patients aged 17 to 60 years, with the highest prevalence in the 21–30 age groups and has male predominance across ages. DNS to the right was the most common finding. A majority of patients showed significant symptom relief postoperatively, with 19 patients achieving complete resolution (no symptoms), 50 improved to mild, 12 to moderate category. Conclusion: Factors including age, gender, persistence of symptom has no significant role in outcome of endoscopic septoplasty as most patient resulted in significant symptom relief. The NOSE score proved to be an effective tool for assessing nasal obstruction, demonstrating a significant reduction of mean postoperatively following endoscopic septoplasty.